Penggunaan Media Sosial Instagram @makanansmr sebagai Media Informasi Kuliner Kota Samarinda - Sari, Yunita; Dwivayani, Kadek Dristiana; Arsyad, Annisa Wahyuni; Purwanti, Silviana (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research titles “Utilizing the Instagram Account @makanansmr as a Culinary Information Platform for Samarinda City” aims to investigate how the owners of the @makanansmr Instagram account anf their followers utilize the account as a source of culinary information in Samarinda. Media users actively employ media to fulfil their needs, ans the motives behind their media usage play a significant role in comprehending the relationship between users and the media they engage with. Ins this study, Uses and Gratification theory was applied, with a specific focus on three motives that drive social media use:information, educational, and entertaiment motives. This research employs a qualitative approach with a descriptive methodology. The findings reveal that the @makanansmr account serves as an effective conduit for culinary information due to the presence of information, educational and entertaiment motives. Beyond serving as a culinary information in making informed decisions about visiting recommended establishments.